Te Waikāmihi ki te Pō, Te Waikāmihi ki te Ao - Hata, Alexandra (Auckland University of Technology, 2010)
The aim of this research is to explore Māori identity and the role of Te Reo Māori in supporting that identity. It is envisaged that this exploration will provide a current analysis of whether Te Reo Māori is still relevant to the development and sustainability of hapū within contemporary Māori society. With the development of the reo at both a hapū and iwi level, the research also seeks to ask how relevant the language is within a contemporary context using Te Tāwera Hapū as a case study. The central theme also examines the complexities of modern-day existence with the traditional, hapū based lifestyle that was based around te reo, whakapapa, kawa, tikanga, hapūtanga, and iwitanga. The anticipated outcome is to inspire hapū development and sustainability from a language paradigm – with a particular emphasis on the development and sustainability of Te Tāwera’s own language and customs. This thesis is written in Te Reo Māori.
Keywords: Te reo Maori; Identity; Contemporary Māori society; Hapū; Whakapapa; Iwi